The burden of mental health illnesses in Kerala: a secondary analysis of reported data from 2002 to 2018 - Jaison Joseph; D. Hari Sankar; Devaki Nambiar (BMC, 2021)
Abstract Background The burden of mental health in India, as in other Low- and Middle-Income Countries (LMICs), is substantial. Secondary Analysis of survey data provides insight into trends in mental health morbidity over time, while administrative data can indicate corresponding trends in availability of infrastructure and services. We compared data from three national level surveys conducted in India to analyse trends in mental health morbidity and available institutional mechanisms to address mental health needs in Kerala, a south Indian state. Methods We compiled data from national and state level population surveys which reported mental health morbidity from 2002 to 2018. We compared the prevalence of mental health illness and disability reported in Kerala with national estimates. We also mapped the most recently available health human resource and infrastructure available in Kerala for mental health care. Basic descriptive statistics were computed for both sets of indicators using Microsoft Excel. Results In 2002, Kerala had 194 persons per hundred thousand population with mental retardation and intellectual disability which increased to 300 persons per hundred thousand population in 2018. The number of individuals with mental health illness in the state increased from 272 person per hundred thousand to 400 persons per hundred thousand in the time period of 2002 to 2018. There were 5.53 beds available per ten thousand persons for treatment in Kerala in 2018. Conclusion Kerala experienced a rapid rise in mental health morbidity between 2002 and 2018. The most recently reported health human resource and infrastructure availability in the state appears to be inadequate to cater to the requirements of mental health care, even as improvements and upgradations are underway. Service and system design changes will have to be mapped and evaluated over time.